GENERALIZED ORLICZ SEQUENCE SPACES - Kustiawan, Cece; Masta, Al Azhary; Dasep, Dasep; Sumiaty, Encum; Fatimah, Siti; Hazmy, Sofihara Al (PATTIMURA UNIVERSITY, 2023)
Orlicz spaces were first introduced by Z. W. Birnbaum and W. Orlicz as an extension of Labesgue space in 1931. There are two types of Orlicz spaces, namely continuous Orlicz spaces and Orlicz sequence spaces. Some of the properties that apply to continuous Orlicz spaces are known, as are Orlicz sequence spaces. This study aims to construct new Orlicz sequence spaces by replacing a function in the Orlicz sequence spaces with a wider function. In addition, this study also aims to show that the properties of the Orlicz sequence spaces still apply to the new Orlicz sequence spaces under different conditions. The method in this research uses definitions and properties that apply to the Orlicz sequence spaces in the previous study and uses the -Young function in these new Orlicz sequence spaces. Furthermore, the results of the study show that the new Orlicz sequence spaces are an extension of the Orlicz sequence spaces in the previous study. And with the characteristics of the -Young function, it shows that the properties of the Orlicz sequence spaces still apply.